The first descriptions of various anatomical structures and embryological remnants of the heart: A systematic overview. (15th January 2017) - Paraskevas, G.; Koutsouflianiotis, K.; Iliou, K.
Abstract: In the present study a brief overview of the history regarding the development of the knowledge of the macroscopic and microscopic anatomical elements of the heart along with some embryological remnants of the heart has been conducted. The evolution of the awareness as regards the various anatomical and embryonic structures of the heart began from Greek medico-philosophers, such as Hippocrates, Herophilus, Erasistratus and Galen, however, such knowledge was enpowered from the meticulous study of philosophers and physicians until the era of modern anatomy. In specific, the following anatomical and embryological structures are displayed: aortic and pulmonary valve, auricles, bundle of Kent, cardiac nerves, conduction system of the heart, ductus arteriosus, intervenous tubercle of Lower, left atrial oblique vein and ligament of Marshall, limbus of fossa ovalis, mitral and tricuspid valve, nodes or nodules of Arantius, ovale foramen, septomarginal trabecula, sinus of Valsava, small cardiac veins or vessels of Thebesius, tendinous chordae and papillary muscles, tendon of the valve of the inferior vena cava and triangle of Koch, valve of the coronary sinus, valve of the inferior vena cava. Highlights: First definitions of heart's structures Comments on each term Misconceptions of the past